The European way since Homer history, memory, identity - Vogel, Jakob 1963-; François, Étienne 1943-; Plitt, Mike 1984-; Serrier, Thomas 1971-; Dörr, Augusta (Bloomsbury Academic, 2021)
Volume 3 investigates the different links between Europe and the rest of the world. There is a focus on Europe's imperial past, as well as the subsequent soft power of Europe and its constant commercial and cultural exchanges with others parts of the world.
Keywords: Geschichte; Kulturaustausch; Auslandsbeziehungen; Wirtschaftsbeziehungen; Europa; Aufsatzsammlung